2018
DOI: 10.1002/jper.16-0712
|View full text |Cite
|
Sign up to set email alerts
|

Classification and diagnosis of aggressive periodontitis

Abstract: Conflicting data resulted for several reasons; 1) the classification was too broad, 2) the disease (AgP) was not studied from its inception, at differing time points (temporal), and at different locations (topographic). New technologic advances coupled with a more delimiting definition of disease will allow for genetic, host and microbial factor analyses in an unbiased manner. As such we predict that progress can be made in identifying a robust group of genetic, host, and microbial risk-markers associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 97 publications
1
56
0
13
Order By: Relevance
“…In the last 30 years, the classification of periodontitis has been repeatedly modified in an attempt to align it with emerging scientific evidence. The workshop agreed that, consistent with current knowledge on pathophysiology, three forms of periodontitis can be identified: necrotizing periodontitis , periodontitis as a manifestation of systemic disease , and the forms of the disease previously recognized as “chronic” or “aggressive”, now grouped under a single category, “periodontitis” . In revising the classification, the workshop agreed on a classification framework for periodontitis further characterized based on a multidimensional staging and grading system that could be adapted over time as new evidence emerges …”
Section: A New Classification Of Periodontitismentioning
confidence: 79%
“…In the last 30 years, the classification of periodontitis has been repeatedly modified in an attempt to align it with emerging scientific evidence. The workshop agreed that, consistent with current knowledge on pathophysiology, three forms of periodontitis can be identified: necrotizing periodontitis , periodontitis as a manifestation of systemic disease , and the forms of the disease previously recognized as “chronic” or “aggressive”, now grouped under a single category, “periodontitis” . In revising the classification, the workshop agreed on a classification framework for periodontitis further characterized based on a multidimensional staging and grading system that could be adapted over time as new evidence emerges …”
Section: A New Classification Of Periodontitismentioning
confidence: 79%
“…11 It is note-worthy from the results of clinical parameters, plaque scores either remained consistent or decreased significantly around teeth and SDIs. The results of the present short follow-up study showed that BOP and CAL around SDIs of the GAgP subjects were significantly higher than in the periodontally healthy subjects.…”
Section: Discussionmentioning
confidence: 91%
“…11 Moreover, periodontal sites harboring Aggregatibacter actinomycetemcomitans demonstrate deeper probing depths (PDs) with or without clinical signs of inflammation. 11 Moreover, periodontal sites harboring Aggregatibacter actinomycetemcomitans demonstrate deeper probing depths (PDs) with or without clinical signs of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, what is the progression of periodontitis in terms of clinical attachment loss, radiographic bone loss, and tooth loss? The reason for limiting the investigation to adults, i.e., persons aged ≥18 years was a request to constrain the investigation in this manner to avoid overlap with a separate investigation into periodontal diseases in younger individuals for the 2017 World Workshop on the Classification of Periodontal and Peri‐Implant Diseases and Conditions …”
Section: Methodsmentioning
confidence: 99%
“…The word “rate” is used here, not in the usual epidemiologic sense of proportion of people affected by a condition, but instead in the sense of how quickly the disease deteriorates. Age of onset is not the topic of this review and will not be addressed further, although is investigated by another review …”
mentioning
confidence: 99%